“It’s Traumatic for All of Us”: A Qualitative Analysis of Providers Caring for Seriously Ill Veterans With Surgical Conditions - Adela Wu, MD; Sarah E. Bradley, PhD, MPH, CPH; C. Ann Vitous, MA, MPH; M. Andrew Millis, MD, MPH; Pasithorn A. Suwanabol, MD, MS (Annals of Surgery Open)
Objective:. We aimed to characterize sources of moral distress among providers in the context of surgery. Background:. Moral distress is defined as psychological unease generated when professionals identify an ethically correct action to take but are constrained in their ability to take that action. While moral distress has been reported among healthcare providers, the perspectives of providers working in surgery specifically are not often explored and reported. Our study was developed from an overarching effort to investigate end-of-life care for seriously ill patients with surgical conditions. Methods:. Using convenience sampling, we conducted 48 semistructured interviews with providers who provide high-intensity care (eg, surgeons, anesthesiologists, intensivists, and midlevel providers) for seriously ill patients with surgical conditions across 14 Veterans Affairs hospitals. Interviews were analyzed iteratively using thematic content analysis. Results:. Providers described clinical encounters that generated moral distress while caring for seriously ill patients with surgical conditions: (1) difficulties in conflict resolution with and among patients and families; (2) specific types of patients or situations; (3) systemic factors hindering appropriate end-of-life care; (4) surgical culture and expectations of the surgeon’s role. Conclusions:. Providers caring for seriously ill patients with surgical conditions report emotions and reactions consistent with moral distress. Our study highlights important triggers for providers and hospital systems to identify and address throughout a surgical provider’s training and career.